Comprehensive analysis of the flavor volatiles and quality characteristics of ginseng products via GC × GC-TOF-MS, aroma profiles and multivariate statistics - Li, Jun; Xu, Xinyi; Zhou, Xinrui; Li, Xiaowen; Guo, Wentao; Lin, Zhe; Lin, He; Piao, Yongge (Frontiers in Nutrition, 2025)
IntroductionAs a popular supplement in the world, ginseng occupies a prominent position in the health food industry. With the expansion of the consumer market, ginseng products have gained wider applications. Previous studies have mainly focused on the cultivation, chemical composition, functions and mechanisms of action of ginseng.MethodsTo explore the differences of flavor quality characteristics of ginseng products, the volatile metabolites of seven products were evaluate from different growth years, growth environments, processing methods, and parts by GC × GC-ToF-MS, sensory evaluation and multivariate statistics.ResultsThe six-year red ginseng exhibited the highest diversity of volatile metabolites with 2,264 compounds identified, followed by ginseng flowers and ginseng under forest. Odour activity values showed that compounds such as 2,3-Butanedione, Pyrazine, and 2-methoxy-3-(1-methylethyl)-, enhanced the pleasant and buttery flavors of ginseng products. And ginseng flowers displayed more pronounced fruity and citrus flavor characteristics. Additionally, the differences of growing year, growing environment, processing methods and parts on flavor characteristics were analyzed by multivariate statistics. The flavor compounds in ginseng products with a low growth period mainly contribute to sweetness and fruity flavor. Ginseng products after steaming and boiling have more attractive sweet characteristics. The differences in the growth environment significantly affect flavor characteristics including sweetness, greenness, fruity, floral, bitter, herbal and waxy.DiscussionThis study provided a vital reference for the establishment of a convenient detection and identification system linking ginseng raw materials, flavor characteristics, volatile compounds, and product quality control.